Study of the interaction between Ξ baryons and light mesons via femtoscopy at the LHC - Abualrob, I. J.; Acharya, S.; Rinella, G. Aglieri; Aglietta, L.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahuja, I.; Akbar, Z. U. L.; Akindinov, A.; Akishina, V.; Al-Turany, M.; et al. (ELSEVIER, 2026)
Meson-baryon systems with strangeness content provide a unique laboratory for investigating the strong interaction and testing theoretical models of hadron structure and dynamics. In this work, the measured correlation functions for oppositely charged Xi-K and Xi-pi pairs obtained in high-multiplicity pp collisions at root s = 13 TeV at the LHC are presented. For the first time, high-precision data on the Xi-K interaction are delivered at small relative momenta. The scattering lengths, extracted via the Lednicky-Lyuboshits expression of the pair wavefunction, indicate a repulsive and a shallow attractive strong interaction for the Xi-K and Xi-pi systems, respectively. The Xi(1620) and Xi(1690) states are observed in the Xi-pi correlation function and their properties, mass and width, are determined. These measurements are in agreement with other available results. Such high-precision data can help refine the understanding of these resonant states, provide stronger constraints for chirally motivated potentials, and address the key challenge of describing the coupled-channel dynamics that may give rise to molecular configurations.
Keywords: Meson-baryon interaction; Strong interaction; Femtoscopy; Strangeness; Molecular states; K-P INTERACTIONS; SIGMA-HYPERON PRODUCTION; CROSS-SECTIONS; CHIRAL DYNAMICS; CHARGE-EXCHANGE; MOMENTUM RANGE; COLLISIONS; RESONANCE; HYDROGEN; STATES; Astronomy & Astrophysics; Physics